Hubungan Pengetahuan dan Sikap Ibu Dengan Status Gizi Selama Kehamilan Trimester Pertama Di PMB M Ginting Kecamatan Siantar Martoba Kabupaten Simalungun Tahun 2023 - Parningotan Simanjuntak; Septimeliani Sihaloho; Asnita Sinaga; Nova Isabela Napitupuluh (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Malnutrition during pregnancy will affect the growth, formation and development of organs as well as the function of the fetus's organs becoming less than optimal, it is feared that congenital defects will occur in the baby being born, it could even result in the baby's head being small due to a lack of fetal nutritional intake for brain development so that brain development is not optimal. Apart from that, infant deaths due to LBW, namely less than 2.5 kg and premature babies, are also due to poor nutritional status of the mother (Nurul Pujiastuti, 2015). This study aims to analyze the relationship between knowledge and attitudes of pregnant women with nutritional status during the first trimester of pregnancy in PMB M Ginting, Siantar Martoba District, Simalungun Regency in 2023. This research is correlational with a cross sectional approach and bivariate data analysis is the data analysis used in the research to find out the relationship or influence of the independent (independent) variable with the dependent (dependent) variable using Chi Square analysis, significant p-value (0.05) (Hardani, 2020) Based on research results Based on the results of statistical tests using Chi-Square, obtained by There There is a relationship between knowledge (p=0.002) of pregnant women and nutritional status during the first trimester of pregnancy and there is a relationship between attitudes (p=0.000) of pregnant women with nutritional status during the first trimester of pregnancy.This means that there is a relationship between the knowledge and attitudes of pregnant women and nutritional status during the first trimester of pregnancy in PMB M Ginting, Siantar Martoba District, Simalungun Regency in 2023.